Differential diagnosis by laboratory medicine : a quick reference for physicians - Marks, Vincent; Mesko, Dusan; Schirger, Alexander (Springer, 2002)
This extensive handbook is indispensable for clinicians and physicians. It provides assistance in the establishment of a precise diagnosis as well as the right decisions for patient treatment. Up-to-date and comprehensive information for differential diagnosis is presented in a well-structured manner. Described in different sections are data of more than 1,950 different conditions, the interference of over 1,200 different drugs as well as a comprehensive section of international reference values of clinical-biochemical and laboratory parameters. The detailed index of more than 900 biochemical/laboratory parameters in various biological samples is especially useful for the practitioner. The extensive list of frequently used synonyms and abbreviations provide comfortable and fast access to desired information.
Keywords: Clinical Laboratory Techniques; chemie, klinická chemie; Diagnosis, Differential; klinické laboratorní techniky; diferenciální diagnóza